Linear viscoelastic studies on a transient network formed by host–guest interaction. Issue 15 (26th June 2018) - Kashiwagi, Yu; Katashima, Takuya; Nakahata, Masaki; Takashima, Yoshinori; Harada, Akira; Inoue, Tadashi
ABSTRACT: A host–guest (HG) polymer was prepared through the radical polymerization of acrylamide monomers (AAm) with a small amount of host‐guest linkers, β‐cyclodextrin‐attached AAm (βCD‐AAm) and adamantane‐attached AAm (Ad‐AAm). The linear viscoelastic and swelling measurements indicated that the resulting HG polymer swollen in water was gel‐like, although the HG polymer is conceptually a linear chain having only temporary crosslinkings. NMR measurements indicated that half of the βCD units incorporated in the HG polymer do not form the inclusion complex with Ad. Rheological analysis of the HG polymer revealed that HG interaction retarded the Rouse modes of networks but did not affect the level of the plateau modulus, which was simply described by the entanglements of AAm chains. This result was confirmed with the reference experiment, in which Ad were capped by competitive βCD molecules. Furthermore, the PAAm polymer with only βCD units (no Ad) was found to exhibit gel‐like behavior. This behavior was attributed to the formation of a small amount of rotaxane structure, which act as permanent crosslinkings, based on 2D NMR data. The HG polymer is basically an entanglement network with temporary sticky points due to the HG interaction, and a few permanent branching points. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1109–1117 Abstract : A host–guest (HG) polymer is a tough supramolecular network using the hydrophobic interaction between β‐cyclodextrin and adamantane units. To clarify the toughening mechanism, rheological and swelling properties are investigated. The HG polymer is an entanglement network with sticky points of the HG complex, which retard the network motion, and branching points formed by rotaxane structures, which make the system solid. This molecular picture helps to prevent the stress concentration of the network strands.